Identification and Characterization of a Novel Rat MAVS Variant Modulating NFκB Signaling - Ihsan Nalkiran; Hatice Sevim Nalkiran (Biomolecules)
The innate immune response serves as the primary defense against viral infections, with the recognition of viral nucleic acids by pattern recognition receptors (PRRs) initiating antiviral responses. Mitochondrial antiviral-signaling protein (MAVS) acts as a pivotal adaptor protein in the RIG-I pathway. Alternative splicing further diversifies MAVS isoforms. In this study, we identified and characterized a novel rat MAVS variant (MAVS500) with a twenty-one-nucleotide deletion, resulting in a protein seven amino acids shorter than the wild-type (WT) rat MAVS. The MAVS500 was cloned from the rat bladder cancer cell line, NBT-II, using specific primers, and subsequently sequenced. MAVS500 was overexpressed in HEK293T and NBT-II cells and then analyzed using Western Blotting and fluorescence microscopy. MAVS500 overexpression increased downstream signaling proteins, NFκβ and pNFκβ, compared to WT rat MAVS in both human and rat cell lines. Structural analysis revealed a high similarity between MAVS500 and WT rat MAVS. The seven-amino-acid deletion in MAVS500 induces significant conformational rearrangements, reducing helical turns and altering structural dynamics, which may impact its interactions with downstream signaling molecules in the innate immune pathway. The identification of MAVS500 enhances our understanding of MAVS regulation and its role in the innate immune response, providing valuable insights into alternative splicing as a mechanism for diversifying protein function.